Comparison of Different Pacing Strategies to Minimize Phrenic Nerve Stimulation in Cardiac Resynchronization Therapy. (26th April 2013) - HUIZAR, JOSE F.; KASZALA, KAROLY; KONERU, JAYANTHI N.; THACKER, LEROY R.; ELLENBOGEN, KENNETH A.
Pacing Strategies to Minimize PN Stimulation: Introduction: Phrenic nerve (PN) stimulation (PNS) frequently limits cardiac resynchronization therapy (CRT). Yet, pacing strategies to minimize PNS have not been systematically compared. We propose to: (1) compare different pacing strategies to minimize PNS in CRT and (2) evaluate differences between PN and left ventricular (LV) capture thresholds among LV pacing configurations. Methods and Results: PN and LV thresholds were obtained using 6 LV configurations in 28 patients with any PNS during CRT implantation or replacement. Incidence of PNS was compared in all LV configurations by programming pacing output to (1) One Volt (V) above LV threshold, (2) triple pulse width (PW) at LV threshold, and (3) 1.5 times LV threshold for each patient. PN thresholds and PN strength‐duration curves were statistically different between configurations (P < 0.05). Ring→RVcoil and Ring→Can had the largest difference between PN and LV thresholds. Pacing output programmed to 1.5 times LV threshold, 1 V above LV threshold, and triple PW at LV threshold had similar probability of PNS between LV configurations. However, 1 V above LV threshold and triple PW at LV threshold frequently resulted in poor (<30%) LV capture safety margin (14–43% and 53–68%, respectively). Freedom from PNS (programmed output at twice LV threshold) was found in 88%, 84%, and 52% with 6, 3, or 2 available LV configurations, respectively. Conclusion: Multiple LV pacing configurations marginally increase the probability of avoiding PNS by electronic reprogramming. Pacing output programmed to 1.5 times LV threshold is an additional alternative to minimize PNS when electronic reprogramming options are limited.